2022
DOI: 10.3390/ijms232012430
|View full text |Cite
|
Sign up to set email alerts
|

Response of Ruminal Microbiota–Host Gene Interaction to High-Altitude Environments in Tibetan Sheep

Abstract: Altitude is the main external environmental pressure affecting the production performance of Tibetan sheep, and the adaptive evolution of many years has formed a certain response mechanism. However, there are few reports on the response of ruminal microbiota and host genomes of Tibetan sheep to high-altitude environments. Here, we conducted an integrated analysis of volatile fatty acids (VFAs), microbial diversity (16S rRNA), epithelial morphology, and epithelial transcriptome in the rumen of Tibetan sheep at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 77 publications
2
6
0
Order By: Relevance
“…(Figures 11 and S8), the content of butyryl-CoA downstream can be reduced, thus affecting the content of butyric acid in the rumens of high-altitude Tibetan sheep. This was consistent with our previous results [14], which also confirmed that rumen microbial metabolites interact with host genes to regulate the body pathway (Figure 11). In addition, differentially expressed genes and metabolites were enriched in the cAMP signaling pathway (Figure S9), which participates in the regulation of the PKA pathway by reducing the level of the metabolite dopamine, resulting in increased expression of the downstream gene CREB5, thus stimulating neurons, regulating body traits, and adjusting to the environmental pressure of plateau mutation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…(Figures 11 and S8), the content of butyryl-CoA downstream can be reduced, thus affecting the content of butyric acid in the rumens of high-altitude Tibetan sheep. This was consistent with our previous results [14], which also confirmed that rumen microbial metabolites interact with host genes to regulate the body pathway (Figure 11). In addition, differentially expressed genes and metabolites were enriched in the cAMP signaling pathway (Figure S9), which participates in the regulation of the PKA pathway by reducing the level of the metabolite dopamine, resulting in increased expression of the downstream gene CREB5, thus stimulating neurons, regulating body traits, and adjusting to the environmental pressure of plateau mutation.…”
Section: Discussionsupporting
confidence: 93%
“…Fructoselysine can be converted to butyric acid [23], which is the main energy substance in ruminants and is involved in ketogenic metabolism [24]. These findings suggest that Tibetan sheep in the 3500 m area are more suitable for grazing and breeding, and similar results were also found in our previous studies [14]. The differential metabolite L-kynurenine decreases with altitude, and studies have found that kynurenine is associated with hypoxia and ischemia in animals [25].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The Tibetan sheep ( Ovis aries ) thrives in harsh environments approximately 3000 m above sea level and represents (Sha et al, 2022). However, the Tibetan sheep face a number of challenges on the Qinghai‐Tibetan Plateau, including prolonged cold weather, low oxygen content in the air, and strong ultraviolet radiation, leading to both growth retardation and poor reproductive performance (Zhou et al, 2022).…”
Section: Introductionmentioning
confidence: 99%